PELAKSANAAN EKSEKUSI HIPOTIK DI PENGADILAN AGAMA MENURUT HUKUM EKONOMI SYARIAH (ANALISIS PUTUSAN PENGADILAN AGAMA SURABAYA NOMOR : 005/PDT.EKS/2018/PA.SBY) - rapi, rusmin; Swadjaja, Isma (Universitas Muhammadiyah Surabaya, 2019)
ABSTRACTThe Religious Court has an important role in the settlement of disputes between the Islamic financial institution and its customers. As the case in the Surabaya Religious Court Number: 005 / Pdt.Eks / 2018 / Pa.Sby, where there was a dispute between PT. Bank BRI Syariah Tbk. as a creditor with PT. Eka Nusa Bahari as the debtor who has defaulted. The formulation of the problem of this research are: First, how is the execution based on sharia economic law in Indonesia and Second, how is the execution in the Surabaya Religious Court in the Sharia Economic Law dispute whether it is in line with Islamic legal principles.This study uses qualitative research methods with a normative juridical approach, namely by using the statutory approach. Normative juridical research, in accordance with the unique character of legal science, lies in the study of the law or legal study of positive law.Based on the results of analysis and research related to the Establishment of the Surabaya Religious Court Number: 005 / Pdt.Eks / 2018 / Pa.Sby, it can be concluded that the implementation of execution based on sharia economic law in Indonesia is the authority of the Religious Court, both in the form of Mortgage, Fiduciary and Mortgage Rights . And the execution in the Surabaya Religious Court in Islamic economic disputes is in line with the principles of Islamic law and in accordance with applicable laws and regulations, but it is expected that the need for higher legal rules, equal to the laws governing the implementation of sharia economic activities in particular mortgage guarantees so that customers as consumers get protection and the Islamic Bank gets a strong legal basis in carrying out its activities.Keywords: Execution, Mortgages, Sharia Economy